Consolidation Characteristics Of Ferrous-Based Metal Powder In Additive Manufacturing - Alkahari, Mohd Rizal; Furumoto, Tatsuaki; Ueda, Takashi; Hosokawa, Akira (The Japan Society of Mechanical Engineers, 2014)
-